Association Between Dietary Total Antioxidant Capacity and Diet Quality in Adults - Salari-Moghaddam, Asma; Nouri-Majd, Saeedeh; Keshteli, Ammar Hassanzadeh; Emami, Fatemeh; Esmaillzadeh, Ahmad; Adibi, Peyman (Frontiers in Nutrition, 2022)
Background: Diet quality is a major contributor to human health. In addition, antioxidants have a great contribution to several chronic conditions. The purpose of this study was to evaluate if dietary total antioxidant capacity (TAC) can be considered as a measure of diet quality in a Middle Eastern country. Methods: In this cross-sectional study on 6,724 Iranian adults, we used a validated food frequency questionnaire (FFQ) to assess dietary intakes. Data derived from the FFQ was used to calculate dietary TAC and well-known diet quality scores including alternate healthy eating index (AHEI) and dietary diversity score (DDS). Dietary TAC was calculated based on the ferric reducing-antioxidant power (FRAP) values reported in earlier publications. AHEI and DDS have also been constructed based on previous publications. Cross-classification was used to examine the agreement between these measures. Results: Mean age and BMI of study participants were 36.89±8.08 y and 24.97±3.87 kg/m2, respectively. We found that individuals in the highest tertile of dietary TAC had higher scores of AHEI (57.53±0.20 vs. 52.03±0.20, P<0.001) and DDS (5.56±0.03 vs. 4.15±0.03, P<0.001) compared with those in the lowest tertile. Participants’ distribution on the basis of the cross-classification analysis indicated that the classifications were in exact agreement for 42.6 %, within an adjacent tertile for 33.05%, and in gross misclassification for 20 % of individuals. When this was examined between dietary TAC and DDS, we found that exact agreement in the classifications was for 59.2 % of participants. Notably, a very low proportion of gross misclassification was seen in this regard such that only 6% of participants were classified in the opposing tertiles, indicating additional support for a good agreement. Conclusion: We found that dietary TAC might be considered as a proper measure for the assessment of diet quality because it was well correlated with well-known measures of diet quality including DDS and AHEI scores.